In-gap states induced by distortion in α-bismuthene. (May 2021) - Lyu, Y.; Daneshmandi, S.; Huyan, S.; Chu, C.-W.
Abstract: Ultrathin Bi(110) films have attracted significant attention recently as potential two-dimensional topological insulators. Their topological band structure induces one-dimensional (1D) helical edge states inside the bulk band gap; however, modification of the density of states resulting from Bi atomic distortion has also been suggested. Here we report the distortion-modified electronic states of α -bismuthene films grown on graphene/6H-SiC(0001) by using low-temperature scanning tunneling microscopy/spectroscopy. We found that the edges along the zigzag boundary between α -bismuthene and graphene are reconstructed and distorted and that the edge states are topographically dependent. The possible trivial origin of edge states induced by distortion complicates the investigation of topological nature in α -bismuthene. Steps from the substrate, stripes, and domain boundaries also induce additional site-dependent in-gap states. Additionally, we located an inversion domain boundary across which atoms are configured in the opposite order. This defect has extended spatial distribution and 1D parabolic dispersion, and hence we suggest it to be a very good platform for further topological exploration in α -bismuthene. Graphical abstract: Image 1 Highlights: Two-dimensional atomically thin α -bismuthene were grown on graphene/6H-SiC(0001) substrate. The zigzag edges in α -bismuthene are reconstructed and distorted and the edge states are topographically dependent. Steps up from the substrate, stripes, and domain boundaries induce additional site-dependent in-gap states. An inversion domain boundary has extended spatial distribution and one-dimensional parabolic dispersion. It would be a very good platform for further topological exploration in α -bismuthene.